Incentives and strategies for financing the renewable energy transition: A review - Sikandar Abdul Qadir (17281241) (2021)
With the global population set to continue growing, the demand for energy will increase. Fossil fuel resources are in decline, and their use is associated with environmental destruction. This highlights the need for more investment in energy resources that can meet the global demand without harming the environment. Clean forms of energy, such as solar, wind, and hydropower, are both successful and readily available, yet investment in them has fluctuated. The affordability, ease of availability and technological maturity of oil in some regions has contributed to the slow uptake of investment in renewable energy projects. This paper discusses the main barriers hindering investment in clean energy production, highlights crucial incentives that could speed up investment processes, and examines several necessary strategies for the transition from fossil-fuel-based energy to renewable sources. Other Information Published in: Energy Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.1016/j.egyr.2021.06.041